PENERAPAN KTSP DAN MUATAN LOKAL DALAM MENINGKATKAN PRESTASI SISWA DI MA NURUR RAHMAH PRAGAAN DAYA SUMENEP TAHUN 2016/2017 - Abd. Qadir; Uswatun Hasanah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2017)
Abstract: Curriculum is one of the guidelines in the teaching and learning process in the world of education. Education can run well when the curriculum becomes the main support in the teaching and learning process. Between KTSP and local content in an education if it is carried out optimally, the results that will be obtained by students will achieve good results. Likewise with the curriculum implemented at MA Nurur Rahmah which uses a combination and combination system. The objectives of this study: 1. To find out the application of KTSP and local content in improving achievement at MA Nurur Rahmah Pragaan Daya Sumenep Academic Year 2016/2017. 2. To find out what are the supporting and inhibiting factors of KTSP and local content in improving student achievement at MA Nurur Rahmah Pragaan Daya Sumenep in the 2016/2017 academic year. The results of the study show that the application of KTSP and local content in improving student achievement uses a combined/combination system between general and religion, namely between local content and national content so that the combination system is very supportive of student knowledge, therefore from the encouragement of the KTSP curriculum and The local content is very sustainable for students' knowledge, so the achievements that students will get will also be a combination, namely there are those who excel in the general and religious fields. While the supporting factors are the quality of the teaching staff who support both the local and national curricula in applying the material, having a vision and mission in accordance with the vision and mission of the institution, the student factor that has above average comprehension so that students' comprehension can help with the achievements that are owned, there is a mutation of parents towards their children. The inhibiting factors are that the curriculum is less relevant to students' mentality, the quality of teaching staff is still below average, lack of support for student programs or for students who lack learning, lack of interest in student learning so that the methods conveyed are not 100% students can only 25% of students get.